The Performance Comparison of European Dttv Standards With Ldpc-Encoded Standard Under Awgn Channel - Karakuş, Oktay (Springer Verlag, 2013)
In this study, in addition to previous work which is a performance comparison of European DTTV Broadcasting standards which are known as DVB-T and DVB-T2, DVB-T2's inner encoder/interleaver block which has LDPC Encoder/Bit Interleaver, is integrated into DVB-T instead of its own inner encoder/interleaver block. This Proposed System's performance under AWGN channel is compared to the DVB-T/T2 standards. The Proposed System achieves better performance results according to DVB-T and very close results according to DVB-T2. It achieves nearly from 4 to 7 decibels SNR gain and up to 13 Mb/s data rate gain then DVB-T results according to different code rate and modulation parameters.
Keywords: AWGN channel; DVB-T; DVB-T2; European DTTV standards; Digital video broadcasting; Performance comparison